Teachers’ Strategies In Teaching Reading Comprehension - Saori, Sopian; Indriana, Pathul; Hikmah, Hikmah (Academy of Education Journal, 2024)
This study is aimed at portraying teacher’s strategies in teaching reading comprehension to students by involving English teachers. The main purpose of the study was to describe the strategies used by english teachers and reveal the strength and weakness of the strategies. This research was a descriptive qualitative research. The design of the study was a case study. The participants of the research were two English teachers who teach in the second grade of junior high schools. Each English teacher had eight meetings that observed by the researcher. To collect the data, there were research instruments: observation, document analysys checklist and interview. They were used to find out the strategies used and how the English teachers applied them in teaching reading comprehension. The result of the study showed that both teachers used almost the same strategies such as brainstorming, reading aloud, and asking for specific information. While the teacher two used nine strategies. They were encouraging the use of dictionaries, reading aloud, reread for checking comprehension, evaluating comprehension in particular tasks, and asking questions for specific information. Both teachers applied and combined the strategies divided into three stages of teaching reading comprehension. The stages were pre-reading stage, while reading stage, and post reading stage. The strategies applied were very effective in teaching reading comprehension in that school. It was proven by the students’ motivation, students’ attention, and teachers’ ease in teaching and learning process.